Study of thickeners synthesized on the basis of polyethoxylate modified with diisocyanates - Глухова, Анна Геннадиевна (Eastern-European Journal of Enterprise Technologies, 2013)
The article studies the new synthetic thickeners of urethane type in pigment printing of fabrics with compositions prepared on the basis of urethane resins. The article presents the influence of the urethane thickeners and the system of solvents used in the preparation on pigment printing quality compared with the standard thickeners. It also presents the influence of organic solvents on the rheological behavior of thickeners based on the urethane thickeners. For the study two different thickeners were prepared using a strong base of the polymer synthesized from polyethoxylate, modified with diisocyanate and two different solvent system for dissolving the solid base and form a solution of thickener. From a solution of the thickener by deterioration of the solvent we obtained a thickener. It was found that the thickener prepared with propylene glycol provides a higher color intensity compared to those the solid base of which was dissolved with ethylene glycol. It was shown that the solvent also affects the stability of the colors to washing and friction, affects the viscosity of the system, the clarity of the contour and painting of underside of the fabric. Effect of thickeners on printing results is explained by their different rheological behavior.